Preliminary observations on abundance and distribution of fish fauna in a canyon of the Bay of Biscay (ICES Division 8c). (9th February 2021) - Diez, G.; Arregi, L.; Basterretxea, M.; Cuende, E.; Oyarzabal, I.
Abstract: The changes in abundance and biodiversity of deep-sea fish fauna are described based on an annual deep-water longline survey with data collected during the period 2015–2019 in the Basque Country continental Slope (ICES Division 8c). The sampling scheme included hauls in four 400 m strata, from 650–2250 m deep. The DST sensors installed in the main line have allowed us to set an accurate soak time for each haul, and they were used to calculate fishing effort and CPUE by haul. The catchability of the fishing gear indicated that 15% of the total hooks deployed in the five-year period were able to fish, and that the bottom longline was very effective in fishing a wide number of different species in all depth ranges. The fishing gear caught 14 different species of sharks (13 deepwater and one pelagic), two chimaeras and nine teleosts. The abundance and biomass registered on the hooks attached to the bottom were between three and four times higher than in the floating sections, and the highest CPUE and biomass were recorded between 1051–1450 m, from 2015 to 2017, and in the 1451–1850 m strata, but they do not show any clear trend throughout the five years of the series.